A systematic review and meta-analysis of GIS use to reveal trends in offshore wind energy research and offer insights on best practices. (August 2020) - Peters, Jared L.; Remmers, Tiny; Wheeler, Andrew J.; Murphy, Jimmy; Cummins, Valerie
Abstract: Offshore wind energy (OWE) is offering an increasingly important contribution to low-carbon energy production to offset anthropogenic global warming due to technological advances that increase the viability of this relatively new industry. These attributes highlight the importance of research being done in this field; however, direct assessments of the research underpinning OWE developments are rare. This systematic review provides a direct assessment of OWE research trends by examining tactics and data employed by a common research tool: Geographic Information Systems (GIS). Clarivate Analytics and Elsevier databases were searched, providing 2668 results that were assessed statistically. The results of the review and meta-analyses highlight several trends, including: (1) <40% of the reviewed studies considered marine spatial planning aspects and <20% mentioned requirements for environmental impact assessments; (2) the maximum viable water depth for fixed-bottom foundations increases steadily over time, ostensibly driven by improved OWE infrastructure development, however this trend is less clear with newer floating technologies; (3) the spatial resolutions of data vary drastically between studies with no relationships in time or between locations; (4) site selection analyses are typified by the most frequent and significant deviations from overall trends in both water depths and spatial resolutions; (5) the number of GIS parameters assessed ranged from 2 to 14 and all studies using >11 parameters employed prescriptive research strategies. These findings allow assessments of overall and research-specific trends that enable suggestions to improve future research compatibilities with disparate study types and actual technology. Highlights: Trends in GIS research specific to offshore wind energy are established. Marine spatial planning and environmental impacts are poorly represented. Spatial resolutions vary between studies with no correlation to time or location. The number of studies per year suggests compatibility between academia and industry. Potential biases could be overcome by adhering to a priori standards or limitations.